Social Housing Competencies: Expertise for a New Era - Michelle Coombs; Isaac Coplan (Canadian Journal of Nonprofit and Social Economy Research, 2018)
This article outlines organizational-level competencies within the changing social housing context in Ontario. The changing context is occurring at the same time as key board members and staff are retiring. This prompts the question of how the sector can ensure excellent housing for low- and middle-income tenants into the future, while keeping in mind its social justice origins. Social constructionist, adult education, and critical theoretical traditions guided the research questions and methodology of this study, resulting in a working definition of organizational competencies. Organizational competencies have been identified through a sequential mixed methods approach. Four key competency clusters have been identified: capital asset, sectoral operational, people-oriented, and strategic. These clusters and the competencies they contain provide a model to assist organizations in meeting their social justice and business goals into the future.